2019
DOI: 10.1037/xhp0000611
|View full text |Cite
|
Sign up to set email alerts
|

Where is the beat in that note? Effects of attack, duration, and frequency on the perceived timing of musical and quasi-musical sounds.

Abstract: Where is the beat in that note? Effects of attack, duration, and frequency on the perceived timing of musical and quasi-musical sounds AbstractWhen coordinating physical actions with sounds, we synchronise our actions with the perceptual center (P-center) of the sound, understood as the specific moment at which the sound is perceived to occur. Using matched sets of real and artificial musical sounds as stimuli, we probed the influence of Attack (rise time), Duration, and Frequency (center frequency) on perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(85 citation statements)
references
References 30 publications
7
73
1
Order By: Relevance
“…This is because there is a distinction between acoustic onset of a sound (which can be subliminal), the perceptual onset (at which point a sound can be detected), and the P-center itself, which is the reference point for where a sound is placed relative to other sounds in a rhythmic sequence (Morton, Marcus, & Frankish, 1976). While originally conceived as a discrete location sometime after the acoustic onset of a sound, subsequent research has shown that P-centers may have some temporal spread and shape (Danielsen et al, 2019;Gordon, 1987;Wright, 2008). Likewise, when a sequence of events occurs, it is the timing between successive P-centers that determines whether the sequence is perceived as regular or irregular.…”
Section: Introductionmentioning
confidence: 99%
“…This is because there is a distinction between acoustic onset of a sound (which can be subliminal), the perceptual onset (at which point a sound can be detected), and the P-center itself, which is the reference point for where a sound is placed relative to other sounds in a rhythmic sequence (Morton, Marcus, & Frankish, 1976). While originally conceived as a discrete location sometime after the acoustic onset of a sound, subsequent research has shown that P-centers may have some temporal spread and shape (Danielsen et al, 2019;Gordon, 1987;Wright, 2008). Likewise, when a sequence of events occurs, it is the timing between successive P-centers that determines whether the sequence is perceived as regular or irregular.…”
Section: Introductionmentioning
confidence: 99%
“…One potential explanation for the instrumental reference leading to lower overall NMA, however, is that the guitar and bass sounds used in the instrumental reference track had longer attack and total durations than the faster and shorter metronome woodblock sounds. Accordingly, as predicted by the findings of research into the perceptual centers of musical sounds (Danielsen et al, 2019;Gordon, 1987;Villing, 2010), the synchronized target location for drummers would be slightly later in the instrumental reference. Regardless, our findings accord with previous studies showing that synchronization to more ecological musical stimuli tends to lead to less NMA than synchronization to metronomic stimuli (Dixon, Goebl, & Cambouropoulos, 2006;Repp, 2008;Wohlschläger & Koch, 2000).…”
Section: Effects Of Timing Style On Onset Locationmentioning
confidence: 78%
“…For pattern 2, an analogously complex and aesthetically appropriate version of the backing track was given, where the guitar pattern was syncopated on the second chord on the ''4-and'' beat, and the alternating quarter-note bass tones were always preceded by eighth-note pick-ups (total duration % 300 ms) ( Figure 3B). While we had no Pcenter data on these guitar and bass sounds, since they all had fast attacks (% 15-25 ms) and previous experiments have shown that P-center of plucked string instruments tend to be close to stimuli onset (Danielsen et al, 2019), all the instrumental reference stimuli were simply aligned to the software grid based on their calculated onset values (see ''Audio Analysis'' sub-section below for onset calculation details).…”
Section: Apparatus and Materialsmentioning
confidence: 99%
See 2 more Smart Citations